ELLIPSE ARC LENGTH - Esmaganbetov M. А.; Kusainova М. M. (Journal of Emerging Technologies and Computing, 2020)
In this article there are ways of studying the integrals that determine the lengths of the arcs of elliptical sculptures, improving the ways to solve them and generalizing the formula that gives an accurate solution in an easy way. The image of the sculpture of an ellipse has been known to us since ancient times, and to this day we do not have a formula for finding the value of its numerical length, which gives us the length of its arc in the correct way, determining the length of its arc in the figure in various ways: in particular, breaking its arc into parts of a rectangle, or trapezoid, knowing that the sets of numbers coming from it are incorrect numbers in advance, we accept them on the basis of numbers close to the actual answer of our calculation. Therefore, in order not to repeat such failures in the future, we consider the following solutions.